Artificial canopy bridges improve connectivity in fragmented landscapes: The case of Javan slow lorises in an agroforest environment. Issue 4 (5th December 2019) - Birot, Hélène; Campera, Marco; Imron, Muhammad Ali; Nekaris, K.A.I.
Abstract: Canopy bridges are increasingly used to reduce fragmentation in tropical habitats yet monitoring of their impact on the behavior of primates remains limited. The Javan slow loris ( Nycticebus javanicus ) is endemic to Java, Indonesia, where the species most often occurs in human‐dominated, highly patchy landscapes. Slow lorises cannot leap, are highly arboreally adapted, and are vulnerable on the ground. To increase arboreal connectivity, as part of a long‐term conservation project in Cipaganti, West Java, we built and monitored seven slow lorises bridges of two types—waterline or rubber—and monitored their use by seven adult individuals from 2016 to 2017. Motion triggered camera traps collected data for 195 ± standard deviation ( SD ) 85 days on each bridge. We collected 341.76 hr (179.67 hr before and 162.09 hr after the installation of bridges) of behavioral and home range data via instantaneous sampling every 5 min, and terrestrial behavior (distance and duration of time spent on the ground) via all occurrences sampling. We found that slow lorises used bridges on average 12.9 ±  SD 9.7 days after their installment mainly for traveling. Slow lorises showed a trend toward an increase in their home range size (2.57 ha before, 4.11 ha after; p  = 0.063) and reduced ground use (5.98 s/hr before, 0.43 s/hr; p  = 0.063) after implementation of bridges. Although the number of feeding trees did not change, new feeding trees were included in the home range, and the proportion of data points spent traveling and exploring significantly decreased ( p  = 0.018). Waterline bridges serve a purpose to irrigate the crops of local farmers who thus help to maintain the bridges, and also ascribe value to the presence of slow lorises. Other endemic mammal species also used the bridges. We advocate the use and monitoring of artificial canopy bridges as an important supplement for habitat connectivity in conservation interventions. Abstract : Research Highlights: We integrated artificial canopy bridges into the home range of Javan slow lorises allowing them to save energy and access new areas. Bridges made of water pipes supplied irrigation to farmers' crops providing additional benefits for local communities.